Micro-Milling of Thin Mould for Continuous Productions of Polymer Microfluidic Devices - Saptaji, Kushendarsyah (Asian Research Publishing Network (ARPN), 2016)
This paper reports an attempt to produce thin embossing mould by using micro-milling process and subsequently tested in fabricating polymer microfluidic devices using hot roller embossing process. Two embossing moulds with thicknesses of 260 μm (thin) and 500 μm (thick) made of Al6061-T6 are fabricated using micro-milling process. The thin and thick moulds subsequently will be used for hot roller embossing process and conventional hot embossing process respectively to produce PMMA microfluidic devices. The performance of the micro-milled thin embossing mould in the hot roller embossing process will be compared with the thick mould used in hot embossing process. The diamond end-mill tool is used for finishing the profile in order to reduce burr formations. The adhesive will be used to hold the thin and thick workpiece in the fabrication of moulds. The experimental results show that the micro-milling is capable to create the features necessary for a microfluidic in thin embossing mould. The thin embossing mould with thickness of about 160 μm with feature height of about 100 μm has been produced successfully using the micro-milling process. The surface quality of the thin embossing mould produced by micro-milling and held using adhesive is comparable with the thick mould.